2014
DOI: 10.1021/jm401992e
|View full text |Cite
|
Sign up to set email alerts
|

Omarigliptin (MK-3102): A Novel Long-Acting DPP-4 Inhibitor for Once-Weekly Treatment of Type 2 Diabetes

Abstract: In our effort to discover DPP-4 inhibitors with added benefits over currently commercially available DPP-4 inhibitors, MK-3102 (omarigliptin), was identified as a potent and selective dipeptidyl peptidase 4 (DPP-4) inhibitor with an excellent pharmacokinetic profile amenable for once-weekly human dosing and selected as a clinical development candidate. This manuscript summarizes the mechanism of action, scientific rationale, medicinal chemistry, pharmacokinetic properties, and human efficacy data for omariglip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
141
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(143 citation statements)
references
References 17 publications
2
141
0
Order By: Relevance
“…Experimental, clinical, and epidemiological studies have shown that type 2 diabetes mellitus is a growing epidemic a ecting approximately 220 million people worldwide [1,2]. The six-members ring B is in the typical chair conformation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental, clinical, and epidemiological studies have shown that type 2 diabetes mellitus is a growing epidemic a ecting approximately 220 million people worldwide [1,2]. The six-members ring B is in the typical chair conformation.…”
Section: Discussionmentioning
confidence: 99%
“…The title compound was prepared by a literature method [1]. 16.5 g (50.4 mmol) of tert-butyl [(2R,3S)-5-oxo-2-(2,5-di uorophenyl)tetrahydro-2H-pyran-3-yl]carbamate, 19.6 g (56.8 mmol) of pyrazole salt (benzenesulfonic acid and 2-(methylsulfonyl)-2,4,5,6-tetrahydropyrrolo [3,4-c]pyrazole) and 250 mL of dimethylacetamide were mixed while stirring.…”
Section: Source Of Materialsmentioning
confidence: 99%
“…The title compound is easily available by a known synthetic protocol [5]. In a typical precepitation reaction 0.3 g of the title compound were dissolved in 5 mL methanol.…”
Section: Source Of Materialsmentioning
confidence: 99%
“…5 Omarigliptin (MK-3102) is a selective, oral DPP-4 inhibitor with a half-life that enables once-weekly dosing that is primarily eliminated by renal excretion. 10 A once-weekly oral antihyperglycaemic agent (AHA) has the potential to provide patients with T2DM an additional option for managing their glycaemic control as part of a patientcentred approach. Omarigliptin has previously been demonstrated to have efficacy comparable to sitagliptin, a marketed daily DPP-4 inhibitor, 11,12 and is approved in Japan.…”
mentioning
confidence: 99%